The passage of Maori land into Pakeha ownership: a Maori view - Williams, Betty Whaitiri (Cabbage Tree, 1983)
Keywords: colonisation; history; kōrero nehe; land alienation; land loss; land march; land tenure; land theft; mana whenua; missionaries

Chapter 6: 'O ratou wenua': Land and Estate Settlements - Warbrick, Paerau (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: mana whenua; tiriti o waitangi/treaty of waitangi; treaty settlements

Tradition and change in Maori leadership - Walker, Ranginui (Research Unit for Maori Education, University of Auckland, 1993)
Keywords: capitalism; colonisation; government; government relations; imperialism; kīngitanga; land loss; land theft; leadership; mana whenua; māori battalion; rangatira; urbanisation

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

Reanimating the strangled rivers of Aotearoa New Zealand - Brierley, Gary J.; Hikuroa, Daniel; Fuller, Ian C.; Tunnicliffe, Jon; Allen, Kristiann; Brasington, James; Friedrich, Heide; Hoyle, Jo; Measures, Richard (WIREs Water, 2022)
Contemporary management practices have artificially confined (strangled) river systems in Aotearoa New Zealand to support intensified land use in riparian areas. These practices work against nature, diminishing the functionality and biodiversity values of living rivers, and associated socio-cultural relations with rivers. River confinement can accentuate flood risk by promoting development in vulnerable locations and limiting the flexibility to adapt to changing climate, prospectively accentuating future disasters. To date, uptake of space-to-move management interventions that seek to address such shortcomings is yet to happen in Aotearoa New Zealand. This is despite the fact that such practices directly align with Māori (indigenous) conceptualizations of rivers as indivisible, living entities. Treaty of Waitangi obligations that assert Māori rights alongside colonial rights of a settler society provide an additional driver for uptake of space-to-move initiatives. This article outlines a biophysical prioritization framework to support the development and roll out of space-to-move interventions in ways that work with the character, behavior, condition, and evolutionary trajectory (recovery potential) of each river system in Aotearoa. This article is categorized under: Water and Life > Conservation, Management, and Awareness Science of Water > Water and Environmental Change
Keywords: environment; environmental protection; mana moana; mana tupuna; mana whenua; mātauranga māori; tikanga | indigenous law; water management

Here to stay: Reshaping the regions through mana Māori - Kukutai, Tahu; Simmonds, Naomi Beth; Ryks, John (Massey University Press, 2016)
Situated 65 kilometres south-east of Hamilton, Putāruru (population 3747 in the 2013 Census) is typical of the many farming service towns scattered across rural Aotearoa New Zealand. Bakeries, op shops, a sports bar and a farm equipment supplier occupy the main street. Unlike nearby Tirau, which transformed from a one-stop shop into a vibrant boutique village in the late 1990s, Putāruru township remains largely indistinguishable from other rural centres. There are few clues to the substantial farming-based and water-generated wealth that lies beyond the town.
Keywords: economic aspects; mana whenua; tino rangatiratanga

'Te Wai-Kaukau o nga matua tipuna': myths, realities, and the determination of mana whenua in the Waikaremoana district. - Wiri, Robert K. J. (ResearchSpace@Auckland, 1994)
In the heart of the North Island of New Zealand lies a mountainous terrain called Te Urewera, the spiritual homeland of the Tϋhoe people. Hidden away in the southern portion of Te Urewera is Waikaremoana, a lake and a land with a history and tradition that are as fascinating as they are controversial. Waikaremoana is the 'tūrangawaewae' of the Ngāti Ruapani section of Tūhoe, and it is they and their lands that are the key focus of this M.A thesis. This thesis deals essentially with the concept of land ownership or mana whenua. It analyses the relationship between customary and colonial concepts of mana whenua in the Waikaremoana district, and examines the conflicting nature of these two different cultural concepts of the land and its history. In many ways this dissertation is unique, as it is a tribal history written by tangata whenua for tangata whenua. It allows today's tangata whenua to see their history through their predecessor's eyes and reawakens the past struggles of their ancestors. It gives tangata whenua a sense of dignity and pride in their heritage and traditions that give them their identity. 'Ko te uri o Tūhoe, moumou kai, moumou tāonga, moumou tangata ki te pō!'
Keywords: iwi; mana whenua; tino rangatiratanga

Opportunities and complexities for Māori and mana whenua representation in local government - Bargh, Maria (Political Science, 2016)
In this article, I outline the existing legislative options available and rationale for M?ori representation in local government. I suggest that the arguments and rationale against M?ori representation have been exacerbated by a lack of clarity around local government?s duties and obligations stemming from the principles of the Treaty of Waitangi. In the second part of this article, I explore more recent arguments by M?ori for representation and involvement in local government decision-making on the basis of being mana whenua, which means to have territorial authority and power associated with the possession and occupation of tribal land. This argument foregrounds specific iwi (tribes) as holding territorial authority and therefore rights to representation and involvement in decision-making sourced in tikanga M?ori (M?ori law), over and above other M?ori who live in that area. I examine in detail the Rotorua District Council?s establishment of the Te Arawa Partnership Board in 2015 and argue that this Board and its first election results provide unique insights into the relationship between Te Arawa people living in and outside the district and has implications for broader conversations about the rights of M?ori living away from their tribal areas.
Keywords: kāwanatanga; local government; mana whenua; political participation; racism; representation; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty principles; voting